Apparent inhibition of induced plant volatiles by a fungal pathogen prevents airborne communication between potato plants. (6th December 2020) - Moreira, Xoaquín; Granjel, Rodrigo R.; de la Fuente, María; Fernández‐Conradi, Pilar; Pasch, Viviana; Soengas, Pilar; Turlings, Ted C. J.; Vázquez‐González, Carla; Abdala‐Roberts, Luis; Rasmann, Sergio
Abstract: Plant communication in response to insect herbivory has been increasingly studied, whereas that involving pathogen attack has received much less attention. We tested for communication between potato ( Solanum tuberosum ) plants in response to leaf infection by the fungal pathogen Sclerotinia sclerotiorum . To this end, we measured the total amount and composition of volatile organic compounds (VOCs) produced by control and infected emitter plants, as well as tested for induced resistance of receiver plants exposed to VOCs from emitters. We further tested for changes in the expression of defensive genes due to pathogen infection. Fungal infection did not significantly affect the total amount or composition of VOCs produced by emitter plants. Correspondingly, we found no evidence of higher resistance to the pathogen in receiver plants exposed to VOCs from infected emitters relative to control emitters. Molecular analyses indicated that pathogen infection drove a down‐regulation of genes coding for VOC precursors, potentially explaining the absence of pathogen effects on VOC emissions and thus of communication. Overall, these results indicate no evidence of airborne communication between potato plants in response to fungal infection and point at pathogen inhibition of VOC emissions as a likely explanation for this result. Abstract : Our results indicate no evidence of communication between potato ( S. tuberosum ) plants in response to pathogen infection and point at pathogen inhibition of VOC emissions as a likely explanation for the observed results.